Water quality, health risk assessment, and treatment options for groundwater in Matsa, Mamvuka and Manyii villages, Limpopo Province - Iwarere, Samuel Ayodele (University of Pretoria, 2025)
Dissertation (MSc (Chemical Technology))--University of Pretoria, 2025.